Motivating Environmentally Conscious Behaviour Through Message Framing - Wylie, Sarah (Université d'Ottawa | University of Ottawa, 2016)
Persuasive communication strategies have offered an effective method to motivate proenvironmental behaviours which have become increasingly necessary to counteract harmful behaviours that threaten the natural environment. This research built on the proposition that self-determination theory and the persuasive messaging technique of message framing could be used together to create highly influential proenvironmental messages that contained the optimal conditions to facilitate both the internalisation of proenvironmental values and the integration of proenvironmental behaviours. Self-determination theory proposed that people have three innate psychological needs (competence, autonomy, and relatedness) and the degree to which these needs are satisfied would influence the quality of people’s motivation, their sense of self-determination, and their performance and maintenance of behaviours. Goal content theory furthered this by distinguishing different types of goals (intrinsic and extrinsic) and their influence on self-determination and future behaviours. This research used message framing to portray a proenvironmental behaviour (reusable mug use) with different goals in order to explore their influence and capacity to motivate behaviour. This was tested by placing posters that promote reusable mug use (framed with either an intrinsic or extrinsic goal) in coffee shops to observe how mug use was influenced by their presence. The results of this study indicated no main effect of the posters however the findings may have been inconclusive to due weaknesses in the study design. Limitations and recommendations are offered.